Business Elites in Panama: Networks, Electoral Contributions, and Revolving Doors - Cárdenas, Julián (2023)
Panama is a particular case in which strong and consolidated regulatory and democratic institutions coexist along with high corruption and state capture. To understand this case, this article analyzes elite’s sources of power: income control, business cohesion, contributions to electoral campaigns and revolving doors. The results show that in Panama there is a very high income concentration together with low fiscal progressivity, cohesion of a small set of family business groups, coordinated contributions to a presidential candidate and appointments of businesspeople to strategic government positions.